2003
DOI: 10.1103/physrevd.68.052005
|View full text |Cite
|
Sign up to set email alerts
|

Observations on muon multiplicity distribution with the GRAPES-2 experiment at Ooty for studies on the mass composition of cosmic rays at PeV energies

Abstract: Precise knowledge of the mass composition of the primary cosmic ray flux below and above the knee in the primary energy spectrum at Eϳ3ϫ10 15 eV is essential for understanding the acceleration and propagation of high energy cosmic rays. Simulations have shown that the correlations between the electron and muon components of showers are very sensitive to the mass of the primary nuclei. In particular, different regions of the muon multiplicity distribution observed with a large area muon detector, for well-defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Some of our earlier results [10] based on the Monte Carlo simulations had indicated that the shape of the muon multiplicity distribution (MMD) measured with a large area muon detector was a sensitive probe of the relative mix of different nuclei in the primary cosmic ray flux [89]. Following this indication, we have attempted to extract the energy spectrum of the protons and other nuclei through a comparison of the observed MMDs with the expectations from the Monte Carlo simulations, for different models of hadronic particle interactions as discussed in the subsequent sections.…”
Section: Cosmic Ray Compositionmentioning
confidence: 83%
See 4 more Smart Citations
“…Some of our earlier results [10] based on the Monte Carlo simulations had indicated that the shape of the muon multiplicity distribution (MMD) measured with a large area muon detector was a sensitive probe of the relative mix of different nuclei in the primary cosmic ray flux [89]. Following this indication, we have attempted to extract the energy spectrum of the protons and other nuclei through a comparison of the observed MMDs with the expectations from the Monte Carlo simulations, for different models of hadronic particle interactions as discussed in the subsequent sections.…”
Section: Cosmic Ray Compositionmentioning
confidence: 83%
“…837 [64,65] and the GRAPES-2 [10] are the other recent experiments using either a large area muon detector or an array of muon detectors with the capability to observe the muon-poor showers. However, the GRAPES-3 experiment [61] with its single large area (560 m 2 ) muon detector is attempting to reach a significantly higher level of sensitivity to the γ-initiated showers based on their small muon content, particularly at the sub-PeV energies, lower than those achieved by the CASA-MIA experiment.…”
Section: High Energy Astroparticle Physics At Ooty and The Grapes-3 Ementioning
confidence: 99%
See 3 more Smart Citations